2012
DOI: 10.1007/s11064-012-0836-8
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Antinociceptive Effects of Oxymatrine and its Effect on Delayed Rectifier K+ Currents (Ik) in PC12 Cells

Abstract: In order to observe antinociceptive effect of Oxymatrine (OMT) and its effect on voltage-activated K(+) channel, the acetic acid-induced abdominal contraction model of mouse was used to test the antinociceptive effect in vivo, and in vitro, the delayed rectifier K(+) currents (Ik) in PC12 cells (rat pheochromocytoma cells) was recorded using the automated patch-clamp method. The results indicated that after application of OMT, the number of acetic acid-induced animal abdominal contraction was significantly dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The voltage-dependent outward potassium current in experimented PC12 cells of present study were elicited by the minor modified protocol based on the described methods by several labs [23,24] on PC12 cells. Some studies have indicated the process of cell death was also accompanied by a large number of potassium ion outflows [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The voltage-dependent outward potassium current in experimented PC12 cells of present study were elicited by the minor modified protocol based on the described methods by several labs [23,24] on PC12 cells. Some studies have indicated the process of cell death was also accompanied by a large number of potassium ion outflows [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, more experiments are needed to fully clarify how Zn 2+ influences glutamate signaling pathway and the voltage-dependent outward potassium ion currents related with neuronal death under hypoxic-ischemic condition. In present study, we have used PC12 cells as model of neuronal cells, which have been used extensively as an experimental A c c e p t e d M a n u s c r i p t 4 system to study various aspects of neurons [21][22][23][24]. We first mimicked the hypoxic-ischemic condition of neuron by Oxygen-Glucose Deprivation (OGD) exposure, and then treated the cells with N, N, N', N'-tetrakis (2-pyridylmethy1) ethylenediamine (TPEN), a specific Zn 2+ chelating agent [25].…”
Section: Page 3 Of 21mentioning
confidence: 99%
“…A concentration of 15.3 μM SF was used to determine the effect of SF on the activation kinetic curves, since at this concentration Ik was inhibited ~50% (close to IC 50 ). For the regression analysis of the activation kinetic curves of Ik, Ik was converted into conductance using the following equation as previously described by Wang et al (16): G = I/(V-Vrev), where G represents conductance, V represents the membrane potential, Vrev represents the reversal potential and I is the K + current. The normalized conductance was shown using the following Boltzmann equation: G/Gmax = {1 + exp[(V1/2−V)/k>, where G/Gmax represents normalized conductance, V1/2 represents membrane potential at half-activation, and k represents slope factor.…”
Section: Methodsmentioning
confidence: 99%
“…The various classes of flavonoids differ in the level of oxidation and the pattern of substitution of the C ring, whereas individual compounds within a class differ in the pattern of substitution of the A and B rings (11). Flavonoids (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) in TCM play an important role in analgesia, and have high application value and prospect.…”
Section: Flavonoidsmentioning
confidence: 99%